Study of Levitation Characteristic against Vertical Displacement at Minimum Levitation Velocity in the Electrodynamic Suspension System with Damper Coils - Higashiike, Shunya; Yamamoto, Ryo; Ohashi, Shunsuke (2023 IEEE International Magnetic Conference - Short Papers (INTERMAG Short Papers), 2023)
The principle of the electrodynamic suspension (EDS) system is electromagnetic induction. The EDS system is used for levitation and guidance of JR Maglev. But a damping factor that only uses the EDS system is small. So, the passive damper system and the semi-active damper system are installed. The bogie starts levitating at 42[m/sec] in this system. The damping factor in that velocity is the smallest at the range of levitation. In this paper, the running simulation when the bogie that runs at minimum levitation velocity passes various vertical displacements is discussed. In the case of vertical displacement is small, the semi-active damper system converges oscillations more than 7[sec] shorter than the passive damper system. However, in the case of the vertical displacement becomes larger, the system that has a positive effect on oscillation suppression becomes passive damper system. The oscillation of the semi-active damper system does not converge. For this reason, the bogie obtains a large damping factor by shifting after reducing the oscillation.